Attitudes and Concerns of Parents as Determinants of Effective Implementation of a Pilot Inclusive Education Project in Winneba, Ghana. - Yeboah, Kofi Asiamah (IJRDO- Journal of Educational Research, 2020)
This study is about parents’ attitudes and concerns as determinants of effective implementation of an inclusive education project in Winneba Ghana. The study seeks to advocate that the existence of positive attitude and concerns on the part of parents is a critical requirement for the effective implementation of inclusive education. The researcher employed a questionnaire and an interview guide to gather data from 110 parents for the study. The data that were analysed showed that the respondents had positive attitudes and strong concerns about the implementation of inclusive education in the pilot schools in the Winneba Municipality. Based on the findings, some recommendations were made to improve upon the attitudes and concerns of parents in the study area.